Rhizospheric Cymbopogon citratus-Staphylococcus succinus interactions for phytoremediation of dibenzofuran-contaminated soil - Nurul Elyni binti Mat Shaari (Kulliyyah of Science, International Islamic University Malaysia, 2018)
Dioxins or dioxin-like compounds is a group of chloroaromatic compounds which considered as the most problematic pollutants and the release of this chemical compound is mainly due to anthropogenic and natural phenomena. It is a highly persistent chemical in environment and accumulates in environment as well as increasing their distribution in our ecosystem. Phytoremediation is one of the tolerable ways that has been operated to battle out the problem of contaminants. This study investigates how plant ecophysiological traits, soil nutrients and microbial activities that will be influenced by dibenzofuran (DBF) pollution in rhizospheric zone of lemon grass as a potential remediator. Lemongrass was planted into uncontaminated soil and DBF-contaminated soil. The topsoil was contaminated with Dibenzofuran (DBF) to a final concentration 100mg/kg. There were four treatments were conducted; soil, soil with plant, soil with bacteria, and soil with plant and bacteria. After one month of exposure, the plant traits such as leaf and root length, aboveground and belowground mass, chlorophyll content and soil enzymes were examined to investigate the sensitivity of lemongrass towards DBF and to evaluate the potential of remediation. With the presence of DBF in soil, leaf and root length, aboveground and belowground mass, chlorophyll content as well as soil enzyme activities were decreased compared to control. However, with inoculation of Staphylococcus succinus in soil, the negative effects of DBF were decreased towards lemongrass growth where the plant growth performance was increased. These results suggest that Staphylococcus succinus capable of degrading DBF and lemongrass is a potential phytoremediator. The present study shows that the combination of lemongrass and Staphylococcus succinus generates an interaction within rhizospheric area that helps the degradation of DBF and increases the lemongrass growth.